2021
DOI: 10.1038/s41598-021-90966-1
|View full text |Cite
|
Sign up to set email alerts
|

Purification of antibody fragments via interaction with detergent micellar aggregates

Abstract: The research described in this report seeks to present proof-of-concept for a novel and robust platform for purification of antibody fragments and to define and optimize the controlling parameters. Purification of antigen-binding F(ab′)2 fragments is achieved in the absence of chromatographic media or specific ligands, rather by using clusters of non-ionic detergent (e.g. Tween-60, Brij-O20) micelles chelated via Fe2+ ions and the hydrophobic chelator, bathophenanthroline (batho). These aggregates, quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…[47][48][49] The conjugated micelle aggregates were found to efficiently purify immunoglobulin G (IgG's), [47][48][49] immunoglobulin M (IgM's), [50] and the F(ab') 2 domain. [51] However, to present a potentially realistic purification platform for the high Ab titers currently achievable by many biotechnology companies, we have now tested this non-chromatographic, ligand-free strategy at IgG concentrations 15-25 mg mL −1 , using a member of one of the commercial, non-ionic detergent families (Tween-20, −40, −60, or −80; Brij-C10, −O20, or −S100), forming a mixed micelle along with the sugar-rich DDM surfactant and tyrosine monomers. Buffer pH values were held close to neutrality (pH 6.5-7) in order to avoid potential acid-induced denaturation of IgG (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…[47][48][49] The conjugated micelle aggregates were found to efficiently purify immunoglobulin G (IgG's), [47][48][49] immunoglobulin M (IgM's), [50] and the F(ab') 2 domain. [51] However, to present a potentially realistic purification platform for the high Ab titers currently achievable by many biotechnology companies, we have now tested this non-chromatographic, ligand-free strategy at IgG concentrations 15-25 mg mL −1 , using a member of one of the commercial, non-ionic detergent families (Tween-20, −40, −60, or −80; Brij-C10, −O20, or −S100), forming a mixed micelle along with the sugar-rich DDM surfactant and tyrosine monomers. Buffer pH values were held close to neutrality (pH 6.5-7) in order to avoid potential acid-induced denaturation of IgG (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The objective of this communication is to present an alternative purification method that would be straightforward to implement, nondenaturing, and would not be compromised by the large size and small diffusion coefficient of IgMs. Accordingly, we studied a nonchromatographic, ligand‐free method that has demonstrated its utility with IgGs and F(ab′) 2 fragments: the active medium is based on micellar aggregates that are formed upon conjugation with amphiphilic [(bathophenanthroline) 3 :Fe 2+ ] complexes (Dhandapani, Howard, et al, 2019; Dhandapani, Nair, et al, 2019; Dhandapani et al, 2020, 2021) Such aggregates were found to: (i) quantitatively capture IgGs (Dhandapani, Howard, et al, 2019; Dhandapani, Nair, et al, 2019; Dhandapani et al, 2020), as well as the F(ab′) 2 domain of a monoclonal antibody (Dhandapani et al, 2021) (presumably due to hydrophobic interactions with the detergent aggregates, in agreement with diverse studies showing how IgGs are purified via hydrophobic interaction chromatography) (Follman & Fahrner, 2004; Ghosh & Wang, 2006; Guse et al, 1994; Manzke et al, 1997); (ii) reject hydrophilic impurities; and (iii) allow efficient recovery of pure antibodies from the detergent aggregates at pH 3.8.…”
Section: Introductionmentioning
confidence: 99%